Nitrosamine Formation Mechanism in Amine-Based CO2 Capture: Experimental Validation. (July 2017) - Supap, Teeradet; Shi, Huancong; Idem, Raphael; Gelowitz, Don; Campbell, Colin; Ball, Max
Abstract: This work presents qualitative experimental validation of nitrosamine mechanism previously proposed by our group which stated that, without nitrogen dioxide (NO2 ), nitrosamine could form from secondary amine reaction with only nitric oxide (NO), oxygen (O2 ), sulfur dioxide (SO2 ) and carbon dioxide (CO2 ). Experimentally, N-nitrosodiethylamine (NDEA) from diethylamine reaction was confirmed by detection in both liquid and gas phases. If diethylamine could form NDEA with only NO, O2, SO2 and CO2, other secondary amines used more commercially (e.g. piperazine (PZ) and its derivatives and diethanolamine) in the capture of CO2 could potentially form their corresponding nitrosamines under similar conditions.